PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP CITIZENSHIP BEHAVIOUR (STUDI KASUS PADA KARYAWAN PT DUTA BETON MANDIRI) - Gali Styowidodo; Abdul Kodir Djaelani; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThe competition between companies is currently very strong, that is why companies are able to create quality and quantity of human resources, which can effective and efficient so that company goals are achieved. There are two important behaviors for a company's progress, namely behavior in and out of the role. Extra-Role Behavior or Organizational Citizenship Behavior (OCB) can maximize the efficiency and productivity of employees and organizations, which effectively become an organization. OCB is a positive behavior of individuals in an organizational that shows an attitude of conscious and voluntary willingness to contribute more to the organization, if formally is required. This study souls to: (1) identify and test the effects of job satisfaction and organizational engagement on the behavior of PT Duta Beton Mandiri employees, (2) the effects of job satisfaction from job satisfaction from job satisfaction on Citizenship Organizations (OCV Organizations) to know and to test) employees of PT Duta Beton Mandiri, (3) Knowing and testing the effect of organizational commitment on Organizational Citizenship Behavior (OCB) employees of PT Duta Beton Mandiri. This research is research with a quantitative approach. The subjects of this study were 57 employees of PT Duta Beton Mandiri. Data collection with questionnaires, interviews and questionnaires. While data analysis was performed using a validity test, a data normality test, a multicollinearity test, a t-test, and a f test and coefficient of determination. The method of analysis uses multiple linear regression analysis. The results of the study at a significance level of 5% indicate that: (1) Job satisfaction and organizational commitment have a positive effect on organizational citizenship behavior (OCB), (2) Job satisfaction has a positive effect on organizational citizenship behavior (OCB), (3) Organizational commitment has a positive effect on organizational citizenship behavior (OCB).So the coefficient of determination (R²) obtained is 0.452. This means that 45.2% Organizational Citizenship Behavior can be explained by the independent variables namely job satisfaction and organizational commitment while the remaining 54.8% Organizational Citizenship Behavior is influenced by other variables not examined in this studyKeywords: job Satisfaction, Organizational Commitment, OCB